Institutional challenges to the implementation of nationally determined contributions in Latin America and Caribbean countries: Institutional architecture requirements, issues arising from the examination of NDC updates and lessons learned from capacity development interventions - Echebarria, Koldo (International Food Policy Research Institute, 2024)
The nations that signed the Paris Agreement periodically submit Nationally Determined Contributions (NDCs) with climate mitigation and adaptation goals. Complementarily, countries should also formulate and implement National Adaptation Plans (NAP) and periodically update them. This means that every country is required by law to outline a course of action in response to global warming and submit a pledge with specific objectives it is committed to achieving. These pledges are then reviewed and renewed every five years. Every round of pledges is meant to intensify the level of commitment and is negotiable, meaning that other parties can offer concessions or support in return for a more robust pledge. The pledge and review method were introduced first in 1991; however, in 1997, the international community chose to adopt legally binding emission reduction targets in the Kyoto Protocol. The pledge and review methods were reintroduced in the 2009 Copenhagen Accord, following its limited success and the inability to reach an agreement on new targets. The NDC wording took the place of the pledge-and-review expression in the negotiations that resulted in the Paris Agreement.